IMPLEMENTASI ASAS REBUS SIC STANTIBUS PADAPERJANJIAN SAAT PANDEMI COVID-19 DAN TERHADAPBERLAKUNYA KEBIJAKAN PEMBERLAKUANPEMBATASAN MASYARAKAT DI INDONESIA - Rafirio Putra; Wardani Rizkianti (Faculty of Law, University of Muhammadiyah Sumatera Utara, 2021)
The Corona pandemic (COVID-19) has prompted the government to issue a policy for the Enforcement of Community Restrictions in Indonesia (PPKM). Which directly has a significant impact on the lives of Indonesian people, especially on aspects of work related to agreements or contracts. Agreements during a pandemic require the role of the Rebus Sic Stantibus Principle to run well. The purpose of this study complements the shortcomings of previous studies by providing an overview of how the implementation of the rebus sic stantibus principle in the agreement during the covid-19 pandemic and whether the cause of the rebus sic stantibus principle must be applied to the agreement during the covid-19 pandemic. The research method uses a juridical-normative method with a conceptual approach to agreements, the principle of rebus sic stantibus and a statutory approach and describes an analysis (descriptive analytical) and is based on the collection of online news selected based on news themes related to the research theme. The results of the study can be concluded that individuals, legal entities and agencies receive direction in implementing the agreement by including the role of the rebus sic stantibus principle and providing an explanation why the rebus sic stantibus principle must be applied to national agreements, especially during the covid-19 pandemic or this PPKM. An important conclusion from this study is the need for the implementation of the rebus sic stantibus principle into national agreements, so that the resolution of the problems in the agreement is not canceled but there is a renegotiation of renegotiations between each party and expects the government to incorporate the principle of rebus sic stantibus into the Civil Code so that it can be used properly in every agreement.